Simple and Cost-Effective Detection of Carbon Monoxide Gas - Setyawati, Onny; Iswanjaya, Septian; Abidin, Zainul; Bahr, Andreas (Journal of Information Technology and Computer Science, 2024)
In several major cities throughout Indonesia, the air pollution represents a significant issue. The escalation of motorized vehicle usage yields increased concentrations of carbon monoxide gas, as one of the primary sources of gas pollution. This study introduced a tool designed and implemented for detecting levels of carbon monoxide gas and providing accurate indications. The tool used an MQ-7 gas sensor in combination with a dot matrix display for this purpose.  The detection apparatus was comprised of an IC 74HC595, an ATMEGA16 microcontroller, a BC557 PNP transistor, and a LED dot matrix. The ATMEGA16 microcontroller served as the primary control device of the system. It received input signals from the MQ-7 gas sensor and subsequently converted them into digital format for display on the dot matrix. The IC 74HC595 and transistor BC557 were utilized as the column controller and line controller, respectively, in the 5x8 LED dot matrix.  The gas level measurement at 0 cm exhibited the lowest error of approximately 0.6 %, measuring 300 ppm CO gas levels. On the other hand, at 10 cm, the result showed approximately an error of 6.7 % for a CO gas level of 200 ppm.